Efeito do sombreamento e da variação estacional sobre o crescimento e produção de óleo essencial em Aloysia triphylla - Menegat, Nadia Regina Volpatto (2013)
The following study was implemented in order to evaluate the effects of different shading levels on the growth and development of Aloysia triphylla plant and the production of essential oil in the four seasons of the year. The experiment was conducted at the Federal University of Santa Maria Campus of Frederico Westphalen, from August 2011 to December 2012. The experimental design was a randomized block design in a factorial scheme with three shading levels (0%, 30% and 50%) and four seasons of the year (summer, autumn, winter and spring). For growth analysis, plants were collected every fortnight. The essential oil was extracted from fresh plant material by steam distillation process, using the modified Clevenger apparatus at the end of each season. For all analyzed variables, it was observed higher growth, production, yield and essential oil content in the season of summer, followed by spring, showing that, in these seasons, the cultivation of Aloysia triphylla may be possible in environments with 30% and 50% shading. Autumn and winter showed low plant growth and essential oil production, and shading decreased further the increase and plant yield.